SYSTEM MECHANISMS OF PHOTOGRAPHY OF OSCILLATORY NETWORKS OF CELLULAR METABOLISM AND HUMAN HEALTH - Mintser, O. P.; Zaliskyi, V. M.; Babintseva, L. Yu. (Medical Informatics and Engineering, 2020)
Background. The study is devoted to understanding the physiological origin of oscillation and the functional role of such oscillations. The purpose of the study was to conceptualize the role of oscillatory signals in different frequency bands by network states. Materials and methods. Results. The circadian clock is a biological oscillator that is present in all photosensitive species. It is able to carry out a 24-hour transcription cycle of light-dark metabolism enzymes. The main question remains: how the central circadian transcription programs of metabolism enzymes are integrated into the physiological responses of individual neurons and how the peripheral circadian oscillator ensembles align the temporal harmonics of the organism's interaction with the environment. The position of the light-regulated network neural oscillators in the SCN circuit and the associated balance of synaptic input may alter membrane potential, Ca2+ level, and cAMP or other signals, thereby determining region-specific variants of «rhythmic» phenotypes observed in natural (in vitro) conditions. The accumulated knowledge of the subtle mechanisms by which SCNs and other parts of the brain adapt to photoperiodic seasonal changes remains incomplete. Along with traditional forms of neuroplasticity (formation of new interneuronal connections, change of synaptic stability and number of synapses), mechanisms of phase neurotransmitter switching between circadian cell oscillators in SCN and in other areas (hypothalamus, hippocampus, 101 hippocampus) are of great importance. Conclusions. Further research may reveal features of how the interaction of these forms of neuronal plasticity (mediated by seasonal changes) participates in the behavioral and physiological responses of oscillatory network photoregulation, optimizing the development of chronotherapy programs as a structural element of systemic biomedicine.